Money, Nominal Contracts, and the Business Cycle: I. One-Period Contract Case - Jang-Ok Cho (Queen's University, Department of Economics, 1990)
A modified version of the nominal contract developed by Gray (1976) and Fischer (1977) is introduced in a general equilibrium model with money which has been used in the real business cycle literature. Money is introduced in the model through cash-in-advance constraint. The contract studied is more efficient than that studied by Gray-Fischer in the sense that the processes involved in the calculation of the nominal contract are not from any other model but from the contract model itself. Two kinds of contract are examined, namely a nominal wage contact and a nominal price contract. A nominal wage contract improves the fit of the model in every respect. In other words, nominal wage contract resolves almost all controversies related to the real business cycle approach. The output volatility increases significantly and the correlation structure becomes much closer to the actual one. However, although a nominal price contract increases the output volatility enormously, it has some unrealistic features. The real and nominal wage rate have very high correlations with output, and a surprise in the technology shock has a negative effect on total hours, output, and real wage rate.
Keywords: 330